To simplify the expression \( 5^9 \cdot 5^{-13} \) using the properties of exponents, we can use the property that states \( a^m \cdot a^n = a^{m+n} \).
So, we combine the exponents: \[ 5^9 \cdot 5^{-13} = 5^{9 + (-13)} = 5^{-4} \]
To write this expression with only positive exponents, we can use the property \( a^{-m} = \frac{1}{a^m} \): \[ 5^{-4} = \frac{1}{5^4} \]
Among the options given, the equivalent expression using only positive exponents is: \[ \frac{1}{5^4} \]
Thus, the correct response is: 1/5^4.